2013
DOI: 10.1515/jpm-2013-0152
|View full text |Cite
|
Sign up to set email alerts
|

Labor induction in nulliparous women with an unfavorable cervix: double balloon catheter versus dinoprostone

Abstract: Induction of labor with the double-balloon catheter in nulliparous women with an unfavorable cervix is associated with a shorter time to delivery compared to dinoprostone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 11 publications
(14 reference statements)
0
32
0
Order By: Relevance
“…Figure summarised the identification and selection process. Of the 152 studies, nine articles were included in the systematic review and meta‐analysis . Details of the characteristics of the included individual studies are demonstrated in Table S1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure summarised the identification and selection process. Of the 152 studies, nine articles were included in the systematic review and meta‐analysis . Details of the characteristics of the included individual studies are demonstrated in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion criteria varied across the records, some studies included only the primiparous, whereas others recruited those who were primiparous or multiparous. Several studies excluded women with twin pregnancy, pre‐eclampsia, oligohydramnios, or history of caesarean section; others did not exclude them . In addition, there were differences between studies with regard to the minimal gestational ages and maximal Bishop scores used for inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Cook Cervical Ripening Balloon was approved by the United States Food and Drug Administration in 2013 and its mechanism is identical to that of the Atad catheter . Single‐balloon (Foley) or double‐balloon (Atad or Cook) catheters are effective mechanical methods for cervical ripening . In a Cochrane meta‐analysis use of a balloon catheter (Foley or COOK) compared to prostaglandins (including misoprostol) for cervical ripening had been found to have decreased tachysystole with fetal heart rate changes .…”
Section: Introductionmentioning
confidence: 99%